Role of Citrullus colocynthis and Psidium guajava Mediated Green Synthesized Silver Nanoparticles in Disease Resistance against Aeromonas hydrophila Challenge in Labeo rohita - Ramsha Hafeez; Zakia Kanwal; Muhammad Akram Raza; Shafqat Rasool; Saira Riaz; Shahzad Naseem; Shifa Rabani; Imran Haider; Naushad Ahmad; Suliman Yousef Alomar (Biomedicines, 2023)
Green synthesis of metallic nanoparticles is an auspicious method of preparing nanoparticles using plant extracts that have lesser toxicity to animal cells and the host. In the present work, we analyzed the antibacterial activity of Citrullus colocynthis and Psidium guajava-mediated silver nanoparticles (Cc-AgNPs and Pg-AgNPs, respectively) against Aeromonas hydrophila (A. hydrophila) in an in vivo assay employing Labeo rohita (L. rohita). L. rohita were divided into six groups for both Cc-AgNPs and Pg-AgNPs treatments separately: Control, A. hydrophila infected, A. hydrophila + Ampicillin, A. hydrophila + Cc/Pg-AgNPs (25 µg/L), A. hydrophila + Cc/Pg-AgNPs (50 µg/L), and A. hydrophila + Cc/Pg-AgNPs (75 µg/L). Changes in different bio-indicators such as hematological, histological, oxidative stress, and cytokine analysis were observed. Interestingly, the infected fish treated with both types of AgNPs (Cc-AgNPs and Pg-AgNPs) exhibited a higher survival rate than the untreated infected fish and demonstrated signs of recovery from the infection, providing a compelling indication of the positive impact of phytosynthesized AgNPs. Disruptions in hematological and histological parameters were found in the infected fish. Both Cc-AgNPs and Pg-AgNPs showed recovery on the hematological and histological parameters. Analysis of oxidative stress and cytokine markers also revealed provoking evidence of the positive impact of Cc-AgNPs and Pg-AgNPs treatment against disease progression in the infected fish. The major finding of the study was that the higher concentrations of the nanoparticles (50 µg/L in the case of Cc-AgNPs and 75 µg/L in the case of Pg-AgNPs) were more effective in fighting against disease. In conclusion, our work presents novel insights for the use of green-synthesized AgNPs as economic and innocuous antibacterial candidates in aquaculture.